2015
DOI: 10.1111/pace.12703
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Ventricular Tachycardia Induction and Mapping for Patients Referred for Epicardial Ablation

Abstract: An initial approach of PES and entrainment mapping under conscious sedation is critically important for patients with NICMP referred for epicardial ablation. Empiric ablation of endocardial/epicardial scar would have missed the clinical VT in 20% of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…More aggressive stimulation was often required with general anesthesia than with conscious sedation ( S6.1.10 ). In another cohort of 25 patients referred for epicardial ablation in the setting of NICM, a strategy of initial programmed stimulation under sedation with midazolam, fentanyl, or remifentanil led to induction of tolerated VT in 15 patients, and avoidance of epicardial access (which was performed under general anesthesia) altogether occurred in 10 (40%) ( S6.1.3 ).…”
Section: Intraprocedural Patient Carementioning
confidence: 99%
See 1 more Smart Citation
“…More aggressive stimulation was often required with general anesthesia than with conscious sedation ( S6.1.10 ). In another cohort of 25 patients referred for epicardial ablation in the setting of NICM, a strategy of initial programmed stimulation under sedation with midazolam, fentanyl, or remifentanil led to induction of tolerated VT in 15 patients, and avoidance of epicardial access (which was performed under general anesthesia) altogether occurred in 10 (40%) ( S6.1.3 ).…”
Section: Intraprocedural Patient Carementioning
confidence: 99%
“…On the basis of the cited single-center observational studies ( S6.1.1 S6.1.3 , S6.1.5 S6.1.11 ) about the various sedative and analgesic strategies for ablation of VAs, it is reasonable to avoid general anesthesia and deeper levels of sedation in patients with idiopathic VAs (PVC or VT) planned for shorter procedures, particularly when the arrhythmia is suspected to be catecholamine-sensitive (typically, automatic and triggered arrhythmias) or was not inducible during a prior procedure. In these patients, a minimal sedation strategy with short-acting sedatives and analgesics, with repeated doses as needed, can be useful to ensure adequate sedation without VA suppression.…”
Section: Intraprocedural Patient Carementioning
confidence: 99%
“…Nazer and colleagues found that an initial programmed electrical stimulation and entrainment mapping under conscious sedation was important for patients with NICM referred for epicardial ablation. In their series, empiric ablation of endocardial and epicardial scar would have missed the clinical VT in 20% of patients ( 75 ).…”
Section: Mapping Strategiesmentioning
confidence: 99%
“…In the earlier phases of my career, I assumed that epicardial ablation had to be performed under general anesthesia and the pericardial puncture with a breath hold. Subsequently, after experiencing my fair share of non-inducibility and hemodynamically unstable VTs under general anesthesia, and with emergence of data that many patients with presumed scar-mediated VT have focal/triggered VTs [1] that may be easier to induce/map/ablate under moderate/ deep sedation [2], and less inducible and hemodynamically stable under general anesthesia [3], my current practice has shifted to performing epicardial procedures under deep sedation when able. In this issue, Conti et al report their single-center experience of 69 patients undergoing epicardial mapping/ablation under conscious sedation with dexmetomidine [4].…”
mentioning
confidence: 99%